2019
DOI: 10.1016/j.eurox.2019.100004
|View full text |Cite
|
Sign up to set email alerts
|

Fractional CO2 laser for treatment of stress urinary incontinence

Abstract: Objectives To evaluate the impact of trans-vaginal fractional CO 2 laser treatment on symptoms of stress urinary incontinence (SUI) in women. Study design Women clinically diagnosed with SUI preferring non-surgical treatment were recruited to the study. Fractional CO 2 laser system (MonaLisa T, DEKA) treatments were administered trans-vaginally every 4–6 weeks for a total of three treatments. Response to treatment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 27 publications
2
35
0
1
Order By: Relevance
“…Vaginal application of CO 2 laser has been recently introduced for medical conditions related to the vaginal epithelium. Most of the studies on vaginal CO 2 laser have been performed for various symptoms under the newly defined broad term “genitourinary syndrome of menopause” (GSM) [7–9] and very few have assessed the efficacy in patients with SUI [10–14]. The promising outcome of SUI treatment in these prospective studies was short term, namely 3–4 months [14], 6 months [13], or slightly longer [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal application of CO 2 laser has been recently introduced for medical conditions related to the vaginal epithelium. Most of the studies on vaginal CO 2 laser have been performed for various symptoms under the newly defined broad term “genitourinary syndrome of menopause” (GSM) [7–9] and very few have assessed the efficacy in patients with SUI [10–14]. The promising outcome of SUI treatment in these prospective studies was short term, namely 3–4 months [14], 6 months [13], or slightly longer [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Gonzalez [11] involving 161 women who underwent scanner‐fractional CO 2 laser treatment, the authors reported statistically significant improvement in ICIQ‐UI‐SF scores and 1‐hour pad weight test at 12, 24, and 36 months ( P < 0.001). Behnia‐Willison et al [12] studied the effect on 58 women and an improvement (mild‐to‐no SUI) reported in 82% of the women at the completion of treatment, but the improvement waned slightly at follow‐up. Lin et al [26] included 31 women in the study; 21 were treated with Er:YAG and 10 women with CO 2 laser and both treatment protocols seemed to be useful for the improvement of SUI symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have referred to the use of nonablative Er:YAG laser for the treatment of SUI [7–9], and one study specified its use for SUI and mixed urinary incontinence (MUI) [10]. CO 2 lasers have been commonly used in clinical practice; however, recently, they have been found to be a valid treatment option for SUI as well [11–14].…”
Section: Introductionmentioning
confidence: 99%
“…2.Our questionnaire on SUI is too simple. Australian Pelvic Floor Questionnaire includes 15 items to reflect Bladder Function [25] , which should be referenced.…”
Section: Discussionmentioning
confidence: 99%